Sifat-Sifat Emping Melinjo Giling dengan Tambahan Bikarbonat dan Bisulfit - Haryadi Haryadi; Supriyanto Supriyanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
Traditional preparation of 'emping melinjo' cracker is hard to develope for production using a high capacity processing machine, besides, the product quality is difficult to control. Effort has been made to solve the problem. Cut sheet `emping melinjo' cracker was made by roasting the `melinjo' nut, dehulling, boiling, grinding, sheet forming, cutting, and drying. NaC1 1.50%, bicarbonate (NaHCO3) ranging from 0.00-1.00%, and bisulfite (NaSO3) ranging from 0-600 ppm were added prior to sheet forming. The raw crackers were characterized for qualitative shelilife, and the fried products for degree of expansion, hygroscopicity, objective texture, and sensoric properties. The results indicated that the addition of NaC1 and NaHS03 gave slightly longer sheiflife. Addition of NaHCO3 resulted in increase in degree of expansion of the fried crackers, but addition of NaHCO3>0,75% caused decrease in cracker expansion after frying. Objective texture, crispness and hygroscopicity were correlated to the level of NaHCO3 addition (r=0.99, 0.99, and 0.98, respectively). The best fitted lines for prediction of objective texture, crispness, and hygroscopicity of the fried crackers were y=7,60-3,50x, y=2,72+1,61x, and y=0,62+0,19x. respectively, where x is the level of NaHCO3 addition. The cut sheet crackers appeared lighter in colour compared to the traditional product, but higher addition of NaHCO3 caused the products more yellowish, yet improved the taste and overall acceptability of the resultant fried crackers. At least addition of NaHCO3 0.50% made the fried crackers preferred by panelists.